Early maladaptive schemas in adolescents with attention deficit hyperactivity disorder - Sireli, Ozlem; Colak, Mehmet; Demirci, Tugce Hilda; Savascihabes, Ayse Ece; Oz Cinar, Hatice (Frontiers in Psychiatry, 2024)
Introduction: Current evidence suggests that early maladaptive schemas are affected in attention deficit hyperactivity disorder (ADHD). Most of the studies on the subject have been conducted with adults, but the number of studies conducted with adolescents with ADHD is quite limited. The aim of this study was to evaluate early maladaptive schemas in adolescents diagnosed with ADHD.The study included 66 patients diagnosed with ADHD and 70 healthy adolescents who were similar to the case group in terms of age and gender. Clinical evaluation of the case and control groups were performed with "The Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime Version, DSM-5 November 2016-Turkish Adaptation (K-SADS-PL-DSM-5-T)". "Conners-Wells Adolescent Self-Report Scale -Revised Short Form (CASS-RS)" and "Set of Early Maladaptive Schema Questionnaires for Children and Adolescents between the ages of 10-16" were administered to all participants.Results: It was determined that the schema scores of "dependence/incompetence", "vulnerability to harm or illness", "entitlement/grandiosity", "insufficient self-control", "subjugation" were significantly higher in the ADHD group than in the control group. A negative, significant relationship was found between age and "enmeshment/undeveloped self", "entitlement/grandiosity" and "insufficient self-control" schema scores. There was no significant difference between schema scores in terms of gender in the ADHD group. Additionally, no significant relationship was found between the education level of the parents, family income levels and schema scores. A significant positive relationship was found between the CASS-RS scores and all schema scores. As a result of the regression analysis, it was determined that CASS-RS scores positively predicted all schema scores, while the age variable negatively predicted only the schema scores of "enmeshment/undeveloped self".Discussion: Results of this study showed that there were significant differences in adolescents in the ADHD group compared to the control group in terms of early maladaptive schemas, and that ADHD symptom levels was associated with early maladaptive schemas.